Magnetic control repair adhesive as well as preparation method and application thereof

By adding components such as epoxy resin, modified phenominal curing agent to the adhesive, the magnetron repair adhesive is formed, which solves the problems of unstable, low strength and easy aging of the existing adhesive, and achieves high Repairing effects of strength and stability.

CN119391340APending Publication Date: 2025-02-07COLLEGE OF ENG TECH HUBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271802.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing adhesives for pipe repair have problems of instability, low strength and prone to aging.

Method used

A magnetron repair adhesive is used, which consists of epoxy resin, modified phenoamine curing agent, aluminum trioxide, heat-resistant filler, nanomagnetic powder, silane-modified polyurethane, hydrated silica and additives, through which The synergistic effect of components significantly improves the strength and stability of the adhesive.

Benefits of technology

This magnetron repair adhesive has high strength and stability, is not easy to age, is suitable for pipeline repair, improving repair effect and engineering efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a magnetic control repair adhesive as well as a preparation method and application thereof, and belongs to the technical field of adhesives. The magnetic control repair adhesive is prepared from the following components in parts by weight: 30 to 50 parts of epoxy resin, 2 to 8 parts of polyfunctional epoxy resin, 30 to 50 parts of modified phenolic aldehyde amine curing agent, 35 to 55 parts of aluminum oxide, 45 to 60 parts of heat-resistant filler, 30 to 50 parts of nano magnetic powder, 15 to 20 parts of silane modified polyurethane, 3 to 15 parts of hydrated silicic acid and 14 to 45 parts of auxiliary agent. The epoxy resin is used as a main component, the modified phenolic aldehyde amine curing agent, the polyfunctional epoxy resin, the aluminum oxide, the heat-resistant filler, the nano magnetic powder, the silane modified polyurethane, the hydrated silicic acid and the auxiliaries are added, and the components have a synergistic effect, so that the prepared magnetic control repair adhesive has relatively high strength and stability. Therefore, the magnetic control repair adhesive has a good application prospect in pipeline repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a magnetic control repair adhesive and a preparation method and application thereof. Background Art

[0002] In modern society, plastic water supply pipes are important facilities for urban water supply. Due to various reasons, pipes often break and leak. When pipes break, it will bring great inconvenience to people's lives. Therefore, it is necessary to repair the broken pipes in time. Traditional repair methods such as welding and replacing pipes are not only costly but also complicated.

[0003] At present, repair adhesives are often used to repair damaged pipes. However, due to the wide variety of urban plastic water supply pipes, repair adhesives need to be used under various underwater temperatures and different water flow rates. Therefore, higher requirements are placed on the performance of repair adhesives.

[0004] Existing adhesives used for pipeline repair still have problems such as instability, low strength and easy aging. Summary of the invention

[0005] The purpose of the present invention is to provide a magnetic control repair adhesive and its preparation method and application, so as to solve the problems of instability, low strength and easy aging of existing adhesives used for pipeline repair.

[0006] In the first aspect, the present invention provides a magnetron repair adhesive, which comprises the following components, in parts by weight: 30-50 parts of epoxy resin, 2-8 parts of multifunctional epoxy resin, 30-50 parts of modified phenolic amine curing agent, 35-55 parts of aluminum oxide, 45-60 parts of heat-resistant filler, 30-50 parts of nano magnetic powder, 15-20 parts of silane-modified polyurethane, 3-15 parts of hydrated silicate, and 14-45 parts of additives.

[0007] In the magnetron repair adhesive provided by the present invention, the epoxy resin may be, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or other values ​​within the range; the multifunctional epoxy resin may be, for example, 2 parts, 4 parts, 6 parts, 8 parts or other values ​​within the range; the modified phenolic amine curing agent may be, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or other values ​​within the range; the aluminum oxide may be, for example, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or other values ​​within the range; the heat-resistant filler may be, for example, 45 parts, 50 parts, 50 parts, 55 parts or other values ​​within the range; The amount of nano magnetic powder can be, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or other values ​​within this range; the amount of silane-modified polyurethane can be, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or other values ​​within this range; the amount of hydrated silica can be, for example, 3 parts, 5 parts, 10 parts, 13 parts, 15 parts or other values ​​within this range; the amount of additives can be, for example, 14 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or other values ​​within this range.

[0008] In the present invention, the inventors have found that epoxy resin has high strength and chemical corrosion resistance, can form a good repair effect with a variety of materials, and can still maintain stable performance under different environments, ensuring that the repair layer has long-term durability; the modified phenolic amine curing agent can react chemically with the epoxy resin to form a stable chemical bond, further improve the strength of the adhesive, and ensure that the repair layer has excellent durability and stability; aluminum oxide can enhance the mechanical properties and corrosion resistance of the adhesive, and can also form a metal-polymer composite structure with the epoxy resin, thereby improving the compressive strength and wear resistance of the repair layer; nano magnetic powder exhibits extremely high magnetic responsiveness, which enables it to respond quickly in a magnetic field and generate strong magnetism, making the repair adhesive more suitable for magnetic control during the repair process, and the nano magnetic powder exhibits good stability under a variety of environments, and can enhance the viscosity of the colloid on the pipeline; hydrated silica can significantly increase the strength of the repair adhesive; the above components significantly improve the strength and stability of the magnetic control repair adhesive through synergistic effects, and the magnetic control repair adhesive is not easy to age.

[0009] In some embodiments, the additives include, by weight: 1-4 parts of epoxidized tung oil toughener, for example, 1 part, 2 parts, 3 parts, 4 parts or other values ​​within the range; 1-3 parts of reactive diluent, for example, 1 part, 2 parts, 3 parts or other values ​​within the range; 1-2 parts of thixotropic agent, for example, 1 part, 1.5 parts, 2 parts or other values ​​within the range; 2-3 parts of accelerator, for example, 2 parts, 2.5 parts, 3 parts or other values ​​within the range; 1-5 parts of vinyl triethoxy silane, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts or other values ​​within the range. Value; 1-4 parts of aminosilane, for example, 1 part, 2 parts, 3 parts, 4 parts or other values ​​within this range; 5-10 parts of nano calcium carbonate, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or other values ​​within this range; 0.1-2 parts of catalyst, for example, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts or other values ​​within this range; 1-4 parts of a mixture of barium sulfate and zinc sulfide, for example, 1 part, 2 parts, 3 parts, 4 parts or other values ​​within this range; 1-4 parts of color paste, for example, 1 part, 2 parts, 3 parts, 4 parts or other values ​​within this range.

[0010] In the present invention, the inventors further discovered that the epoxidized tung oil toughening agent has the effects of dilution and plasticization, which can improve the construction performance of the adhesive, making it easier to apply and evenly distribute; at the same time, it can also improve the flexibility and low-temperature resistance of the repair adhesive, making the repair layer more adaptable to various complex environments; aminosilane has thickening and thixotropic effects, which can improve the consistency and stability of the adhesive, and prevent stratification or precipitation during storage and use; the catalyst can accelerate the curing process of the adhesive and increase the curing speed of the adhesive, which helps to shorten the repair time and improve engineering efficiency; the above components significantly improve the performance of the magnetic control repair adhesive through synergistic effects.

[0011] In some embodiments, the epoxy resin includes at least one of a phenolic epoxy resin and a bisphenol A epoxy resin; the modified phenolic amine curing agent is obtained by a Mannich reaction of a polyamine, an alkylphenol and a paraformaldehyde, and the molar ratio of the polyamine, the alkylphenol and the paraformaldehyde is (0.8-1.2):(0.6-1):(0.8-1.2), for example, it can be 0.8:0.6:0.8, 0.8:0.8:1, 0.8:1:1.2, 1:0.6:0.8, 1:0.8:1, 1:1:1.2, 1.2:0.6:0.8, 1.2:0.8:1, 1.2:1:1.2 or other ratios within the range. value; the polyamine is selected from at least one of hexylene diamine, ethylenediamine, diethylenetriamine, triethylenetetramine, methylcyclopentanediamine and meta-xylylenediamine, and the alkylphenol includes dodecylphenol; the multifunctional epoxy resin is selected from at least one of TDE-85 and AG-80; the particle size of aluminum oxide is 100-1000nm, for example, it can be 100nm, 200nm, 400nm, 600nm, 800nm, 1000nm or other values ​​within this range; the nano magnetic powder includes ferroferric oxide nano magnetic powder; the silane-modified polyurethane is obtained by reacting a polyether polyol and a diisocyanate under the action of a catalyst and then using silane for end-capping.

[0012] In some embodiments, the epoxy resin includes a phenolic epoxy resin and a bisphenol A epoxy resin, and the mass of the phenolic epoxy resin accounts for 20-40% of the mass of the epoxy resin; the phenolic epoxy resin is selected from at least one of NPPN-638S, F-44 and F-51; the particle size of the ferrosoferric oxide nanoparticles is 5-500nm, for example, 5nm, 10nm, 100nm, 200nm, 300nm, 400nm, 500nm or other values ​​within the range; silane In the preparation process of the modified polyurethane, the mass ratio of the polyether polyol, the diisocyanate and the catalyst is (3-5): (0.8-1.2): (0.03-0.07), for example, it can be 3:0.8:0.03, 3:1:0.05, 3:1.2:0.07, 4:0.8:0.03, 4:1:0.05, 4:1.2:0.07, 5:0.8:0.03, 5:1:0.05, 5:1.2:0.07 or other ratios within this range.

[0013] In some embodiments, the epoxidized tung oil toughener is obtained by epoxidation of tung oil, petroleum ether and formic acid in the presence of a catalyst. The epoxidation value of the epoxidized tung oil toughener is 7-8%, for example, 7%, 7.5%, 8% or other values ​​within the range; and the mass ratio of tung oil, petroleum ether, formic acid and catalyst is (13-17): (8-12): (3-7): (0.5-1.5), for example, 13:8:3:0.5, 13:10:5:1, 13:12:7:1.5, 15:8:3:0.5, 15:10:5 :1, 15:12:7:1.5, 17:8:3:0.5, 17:10:5:1, 17:12:7:1.5 or other ratios within this range; the catalyst includes sulfuric acid; the particle size of nano calcium carbonate is 0.01-0.1μm, for example, it can be 0.01μm, 0.03μm, 0.05μm, 0.07μm, 0.1μm or other values ​​within this range; the catalyst is selected from at least one of tin butyrate and dibutyltin dioctoate; the barium sulfate and zinc sulfide mixture is obtained by reacting zinc, water and sulfuric acid to obtain zinc sulfate, and then mixing the zinc sulfate with the barium sulfide solution to react.

[0014] In a second aspect, the present invention provides a method for preparing a magnetron repair adhesive as described above, comprising the following steps: providing silane-modified polyurethane, epoxidized tung oil toughening agent, modified phenolic amine curing agent and a mixture of barium sulfate and zinc sulfide respectively; mixing epoxy resin, multifunctional epoxy resin, reactive diluent and epoxidized tung oil toughening agent and stirring evenly, then sequentially adding aluminum oxide and thixotropic agent, continuing stirring and mixing to obtain an intermediate mixture; continuing to add modified phenolic amine curing agent and accelerator to the intermediate mixture, stirring evenly, then sequentially adding heat-resistant filler and vinyl triethoxysilane, continuing stirring and mixing; then adding silane-modified polyurethane, hydrated silica, aminosilane, nano-calcium carbonate, a mixture of barium sulfate and zinc sulfide, a catalyst, ferrosoferric oxide nano-magnetic powder and color paste, stirring evenly to obtain a magnetron repair adhesive.

[0015] In the present invention, the raw materials used are cheap and easily available, and the preparation process is simple, so it has good application prospects in large-scale industrial production.

[0016] In some embodiments, the preparation method of silane-modified polyurethane provided comprises: placing a polyether polyol at a temperature of 100-140°C (for example, 100°C, 120°C, 140°C or other values ​​within the range), dehydrating for 2-4h, for example, 2h, 3h, 4h or other values ​​within the range; then cooling to 75-85°C, for example, 75°C, 80°C, 85°C or other values ​​within the range; adding diisocyanate and a catalyst, reacting for 1-3h, for example, 1h, 2h, 3h or other values ​​within the range; and detecting the NCO content, and finally adding silane to react until there is no free NCO to obtain a silane-modified polyurethane.

[0017] In some embodiments, the preparation method of the provided epoxidized tung oil toughener includes: mixing tung oil, petroleum ether, formic acid and a catalyst, heating to 50-55°C (for example, 50°C, 53°C, 55°C or other values ​​within the range), adding hydrogen peroxide dropwise, continuing to heat to 60-65°C (for example, 60°C, 63°C, 65°C or other values ​​within the range) and keeping the temperature for reaction for 5-7h, for example, 5h, 6h, 7h or other values ​​within the range; after purifying the obtained product, the epoxidized tung oil toughener is obtained.

[0018] In some embodiments, the preparation method of the modified phenolic amine curing agent provided comprises: mixing an alkylphenol and a polyamine, stirring and heating to 65-75°C, for example, 65°C, 70°C, 75°C or other values ​​within the range; then adding polyformaldehyde, stirring and reacting for 2-4h, for example, 2h, 3h, 4h or other values ​​within the range, at a temperature of 65-70°C (for example, 65°C, 67°C, 70°C or other values ​​within the range); then stirring and reacting for 1-3h, for example, 1h, 2h, 3h or other values ​​within the range, at a temperature of 75-80°C (for example, 75°C, 77°C, 80°C or other values ​​within the range); and obtaining the modified phenolic amine curing agent.

[0019] In some embodiments, the preparation method of the provided mixture of barium sulfate and zinc sulfide includes: mixing zinc and water in a mass ratio of (2-4):1 (for example, it can be 2:1, 3:1, 4:1 or other ratios within the range) and heating to a temperature of 65-70°C, for example, 65°C, 67°C, 70°C or other values ​​within the range; adding sulfuric acid to react to obtain a zinc sulfate solution, mixing the zinc sulfate solution with a barium sulfide solution, and adjusting the pH to 7.6-8.0 (for example, it can be 7.6, 7.8, 8.0 or other values ​​within the range) to perform a precipitation reaction to obtain a mixture of barium sulfate and zinc sulfide.

[0020] In some embodiments, during the preparation of the intermediate mixture, the stirring and mixing time is 30-40 min, for example, 30 min, 32 min, 35 min, 37 min, 40 min or other values ​​within the range.

[0021] In some embodiments, during the preparation of the magnetron repair adhesive, the stirring and mixing time is 30-60 min, for example, 30 min, 40 min, 50 min, 60 min or other values ​​within the range.

[0022] In a third aspect, the present invention provides a use of any of the above-mentioned magnetically controlled repair adhesives in pipeline repair.

[0023] The beneficial effect of the present invention is that, different from the prior art, the present invention uses epoxy resin as the main component, and simultaneously adds modified phenolic amine curing agent, multifunctional epoxy resin, aluminum oxide, heat-resistant filler, nano magnetic powder, silane-modified polyurethane, hydrated silicate and additives. The above components act synergistically to make the prepared magnetic control repair adhesive have high strength and stability and are not easy to age. Therefore, the magnetic control repair adhesive has a good application prospect in pipeline repair. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.

[0026] In the present invention, the silane-modified polyurethane is prepared by the following method: 100g of polyether polyol is placed at a temperature of 120°C, dehydrated for 3h, then cooled to 80°C, 25g of diisocyanate and 1.25g of dibutyltin dilaurate are added, reacted for 1-3h, and the NCO content is detected, and finally 10g of γ-propyltriethoxysilane is added to react until there is no free NCO, thereby obtaining the silane-modified polyurethane.

[0027] The epoxidized tung oil toughening agent is prepared by the following method: tung oil, petroleum ether, formic acid and concentrated sulfuric acid are mixed in a three-necked flask with a stirrer, a condenser and a thermometer in a mass ratio of 15:10:5:1, and the temperature is raised to 55°C and then hydrogen peroxide is added dropwise; after the addition is completed, the temperature is raised to 60°C and kept warm for reaction for 6 hours; after the reaction is completed, the product is transferred to a separatory funnel and allowed to stand for stratification; the oil layer is washed with sodium hydroxide solution to pH>8, then washed with deionized water to neutrality, and then dried with anhydrous magnesium sulfate for 24 hours; after filtering, the filtrate is distilled under reduced pressure at 75°C, and after cooling to room temperature, the epoxidized tung oil toughening agent is obtained, and its epoxy value is about 7-8%.

[0028] The modified phenolic amine curing agent is prepared by the following method: dodecylphenol and diethylenetriamine are mixed, stirred and heated to 70°C, and then polyformaldehyde is added, and the reaction is stirred for 3 hours at a temperature of 65°C, and then stirred for 2 hours at a temperature of 75°C to obtain the modified phenolic amine curing agent, wherein the molar ratio of diethylenetriamine, dodecylphenol and polyformaldehyde is 1:0.8:1.

[0029] The barium sulfate and zinc sulfide mixture is prepared by the following method: zinc and water are mixed in a mass ratio of 3:1 and heated to a temperature of 70°C, sulfuric acid is added for reaction to obtain a zinc sulfate solution, the zinc sulfate solution and the barium sulfide solution (barium sulfide is slowly added into boiling water to form a solution with a mass concentration of 35%) are mixed in a mass ratio of 7:3, and the pH is adjusted to 7.8 for precipitation reaction, the product is placed in an oven and dried at 100°C for 60 minutes to obtain a barium sulfate and zinc sulfide mixture.

[0030] Example 1 A magnetron repair adhesive comprises the following components, measured in parts by weight: 6 parts of NPPN-638S, 24 parts of bisphenol A epoxy resin, 30 parts of modified phenolic amine curing agent, 2 parts of TDE-85, 30 parts of ferroferric oxide nano magnetic powder, 15 parts of silane-modified polyurethane, 3 parts of hydrated silicate, 1 part of epoxidized tung oil toughening agent, 35 parts of aluminum oxide, 45 parts of heat-resistant filler, 1 part of active diluent, 1 part of thixotropic agent, 2 parts of accelerator, 1 part of vinyl triethoxysilane, 1 part of aminosilane, 5 parts of nano calcium carbonate, 0.5 parts of tin butyrate, 1 part of a mixture of barium sulfate and zinc sulfide, and 1 part of color paste.

[0031] The preparation method of the magnetic control repair adhesive comprises the following steps: S1. After NPPN-638S, bisphenol A epoxy resin, TDE-85, active diluent and epoxidized tung oil toughening agent are mixed and stirred evenly, aluminum oxide with a particle size of 1000 nm and a thixotropic agent are added in sequence, and the mixture is stirred and mixed for 35 minutes to obtain an intermediate mixture; S2. Continue to add modified phenolic amine curing agent and accelerator to the intermediate mixture, stir evenly, then add heat-resistant filler and vinyl triethoxysilane in turn, and continue stirring and mixing for 50 minutes; then add silane-modified polyurethane, hydrated silica, aminosilane, nano-calcium carbonate with a particle size of 0.1 μm, a mixture of barium sulfate and zinc sulfide, tin butyrate, nano-iron tetroxide magnetic powder with a particle size of 500 nm and color paste, stir evenly, and obtain a magnetron repair adhesive.

[0032] Example 2 A magnetron repair adhesive comprises the following components, measured in parts by weight: 12 parts of F-44, 28 parts of bisphenol A epoxy resin, 40 parts of modified phenolic amine curing agent, 5 parts of AG-80, 40 parts of ferroferric oxide nano magnetic powder, 18 parts of silane-modified polyurethane, 8 parts of hydrated silicate, 2 parts of epoxidized tung oil toughening agent, 45 parts of aluminum oxide, 53 parts of heat-resistant filler, 2 parts of active diluent, 1.5 parts of thixotropic agent, 2.5 parts of accelerator, 3 parts of vinyl triethoxysilane, 2 parts of aminosilane, 8 parts of nano calcium carbonate, 1 part of dibutyltin dioctoate, 2 parts of a mixture of barium sulfate and zinc sulfide, and 2 parts of color paste.

[0033] The preparation method of the magnetic control repair adhesive comprises the following steps: S1. F-44, bisphenol A epoxy resin, AG-80, active diluent and epoxidized tung oil toughening agent were mixed and stirred evenly, and then aluminum oxide with a particle size of 500 nm and a thixotropic agent were added in sequence, and the mixture was stirred and mixed for 35 minutes to obtain an intermediate mixture; S2. Continue to add modified phenolic amine curing agent and accelerator to the intermediate mixture, stir evenly, then add heat-resistant filler and vinyl triethoxysilane in turn, and continue stirring and mixing for 50 minutes; then add silane-modified polyurethane, hydrated silica, aminosilane, nano-calcium carbonate with a particle size of 0.05 μm, a mixture of barium sulfate and zinc sulfide, dibutyl tin dioctoate, nano-iron oxide magnetic powder with a particle size of 250 nm and color paste, stir evenly, and obtain a magnetron repair adhesive.

[0034] Example 3 A magnetron repair adhesive comprises the following components, measured in parts by weight: 20 parts of F-51, 30 parts of bisphenol A epoxy resin, 50 parts of modified phenolic amine curing agent, 8 parts of TDE-85, 50 parts of ferroferric oxide nano magnetic powder, 20 parts of silane-modified polyurethane, 15 parts of hydrated silica, 4 parts of epoxidized tung oil toughening agent, 55 parts of aluminum oxide, 60 parts of heat-resistant filler, 3 parts of active diluent, 2 parts of thixotropic agent, 3 parts of accelerator, 5 parts of vinyl triethoxysilane, 4 parts of aminosilane, 10 parts of nano calcium carbonate, 2 parts of dibutyltin dioctoate, 4 parts of a mixture of barium sulfate and zinc sulfide, and 4 parts of color paste.

[0035] The preparation method of the magnetic control repair adhesive comprises the following steps: S1. F-51, bisphenol A epoxy resin, TDE-85, active diluent and epoxidized tung oil toughening agent were mixed and stirred evenly, and then aluminum oxide with a particle size of 100 nm and a thixotropic agent were added in sequence, and the mixture was stirred and mixed for 35 minutes to obtain an intermediate mixture; S2. Continue to add modified phenolic amine curing agent and accelerator to the intermediate mixture, stir evenly, then add heat-resistant filler and vinyl triethoxysilane in turn, and continue stirring and mixing for 50 minutes; then add silane-modified polyurethane, hydrated silica, aminosilane, nano-calcium carbonate with a particle size of 0.01 μm, a mixture of barium sulfate and zinc sulfide, dibutyl tin dioctoate, nano-iron tetroxide magnetic powder with a particle size of 5 nm and color paste, stir evenly, and obtain a magnetron repair adhesive.

[0036] Comparative Example 1 The magnetic control repair adhesive and its preparation method in this comparative example are basically the same as those in Example 3, except that no modified phenolic amine curing agent is added.

[0037] Comparative Example 2 The magnetron repair adhesive and its preparation method in this comparative example are basically the same as those in Example 3, except that hydrated silica is replaced by fumed silica.

[0038] Performance Testing The thermal conductivity, shear strength, and double 85 aging 2000h shear strength of the magnetron repair adhesives prepared in Examples 1-3 and Comparative Examples 1-2 were tested, wherein the thermal conductivity was tested using the method specified in ASTM D5470-2006, and the shear strength and double 85 aging 2000h shear strength were tested using the method specified in GB / T 7124-2008; the specific test results are shown in Table 1 below: Table 1 Thermal conductivity, shear strength and double 85 aging 2000h shear strength test results

[0039] It can be seen from the data in Table 1 that the magnetron repair adhesive prepared in Examples 1-3 has good thermal conductivity and high shear strength. In Comparative Example 1, no modified phenolic amine curing agent was added. The results showed that the shear strength of the prepared magnetron repair adhesive was significantly reduced, and during the double 85 aging 2000h shear strength test, it failed at 23d. The results further showed that by adding modified phenolic amine curing agent, the strength of the magnetron repair adhesive can be further improved; in Comparative Example 2, hydrated silica was replaced with fumed silica. The results showed that the shear strength of the prepared magnetron repair adhesive was significantly reduced, and during the double 85 aging 2000h shear strength test, it failed at 28d. The results further showed that adding hydrated silica can further improve the strength of the magnetron repair adhesive.

[0040] The magnetron repair adhesives prepared in Examples 1-3 and Comparative Examples 1-2 were respectively placed between two substrates (the substrates were made of polypropylene, polyethylene and polystyrene, respectively) for adhesion, and then immersed in water at 25°C for 24 hours, and then the shear strength was tested using a tensile testing machine. The results are shown in Table 2 below: Table 2 Shear strength test results

[0041] From the data in Table 2, it can be seen that the magnetron repair adhesives prepared in Examples 1-3 have good strength when adhering to substrates of different materials. In Comparative Example 1, no modified phenolic amine curing agent was added. It was found that the shear strength of the prepared magnetron repair adhesive was significantly reduced. The results further showed that the strength of the magnetron repair adhesive can be further improved by adding a modified phenolic amine curing agent; in Comparative Example 2, hydrated silica was replaced with fumed silica. It was found that the shear strength of the prepared magnetron repair adhesive was significantly reduced. The results further showed that the addition of hydrated silica can further improve the strength of the magnetron repair adhesive.

[0042] In summary, the magnetic control repair adhesive of the present invention has high strength and stability and is not prone to aging. Therefore, the magnetic control repair adhesive has a good application prospect in pipeline repair.

[0043] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0044] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A magnetic control repair adhesive, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of epoxy resin, 2-8 parts of multifunctional epoxy resin, 30-50 parts of modified phenolic amine curing agent, 35-55 parts of aluminum oxide, 45-60 parts of heat-resistant filler, 30-50 parts of nano magnetic powder, 15-20 parts of silane-modified polyurethane, 3-15 parts of hydrated silicate and 14-45 parts of auxiliary agent.

2. The magnetic control repair adhesive according to claim 1, characterized in that: In parts by weight, the auxiliary agent includes: 1-4 parts of epoxidized tung oil toughener, 1-3 parts of active diluent, 1-2 parts of thixotropic agent, 2-3 parts of accelerator, 1-5 parts of vinyl triethoxysilane, 1-4 parts of aminosilane, 5-10 parts of nano calcium carbonate, 0.1-2 parts of catalyst, 1-4 parts of a mixture of barium sulfate and zinc sulfide, and 1-4 parts of color paste.

3. The magnetic control repair adhesive according to claim 1, characterized in that: The epoxy resin includes at least one of a novolac epoxy resin and a bisphenol A epoxy resin; The modified phenolic amine curing agent is obtained by a Mannich reaction of a polyamine, an alkylphenol and polyformaldehyde, and the molar ratio of the polyamine, the alkylphenol and the polyformaldehyde is (0.8-1.2): (0.6-1): (0.8-1.2), the polyamine is selected from at least one of hexylene diamine, ethylene diamine, diethylene triamine, triethylene tetramine, methyl cyclopentane diamine and meta-xylene diamine, and the alkylphenol includes dodecylphenol; The multifunctional epoxy resin is selected from at least one of TDE-85 and AG-80; The particle size of the aluminum oxide is 100-1000nm; The nano magnetic powder includes ferroferric oxide nano magnetic powder; The silane-modified polyurethane is obtained by reacting polyether polyol and diisocyanate under the action of a catalyst and then using silane for end-capping.

4. The magnetic control repair adhesive according to claim 3, characterized in that: The epoxy resin includes novolac epoxy resin and bisphenol A epoxy resin, and the mass of the novolac epoxy resin accounts for 20-40% of the mass of the epoxy resin; The phenolic epoxy resin is selected from at least one of NPPN-638S, F-44 and F-51; The particle size of the ferroferric oxide nanoparticles is 5-500 nm; During the preparation of the silane-modified polyurethane, the mass ratio of the polyether polyol, the diisocyanate and the catalyst is (3-5): (0.8-1.2): (0.03-0.07).

5. The magnetic control repair adhesive according to claim 2, characterized in that: The epoxidized tung oil toughening agent is obtained by epoxidation of tung oil, petroleum ether and formic acid under the catalysis of a catalyst. The epoxidation value of the epoxidized tung oil toughening agent is 7-8%, and the mass ratio of the tung oil, petroleum ether, formic acid and catalyst is (13-17): (8-12): (3-7): (0.5-1.5), and the catalyst includes sulfuric acid; The particle size of the nano calcium carbonate is 0.01-0.1 μm; The catalyst is selected from at least one of tin butyrate and dibutyltin dioctoate; The barium sulfate and zinc sulfide mixture is obtained by reacting zinc, water and sulfuric acid to obtain zinc sulfate, and then mixing the zinc sulfate with a barium sulfide solution to react.

6. A method for preparing the magnetic control repair adhesive according to any one of claims 1 to 5, characterized in that: The steps include: Silane-modified polyurethane, epoxidized tung oil toughening agent, modified phenolic amine curing agent and a mixture of barium sulfate and zinc sulfide are provided respectively; After epoxy resin, multifunctional epoxy resin, active diluent and epoxidized tung oil toughening agent are mixed and stirred evenly, aluminum oxide and thixotropic agent are added in sequence, and stirring and mixing are continued to obtain an intermediate mixture; The modified phenolic amine curing agent and accelerator are continuously added to the intermediate mixture, and after being evenly stirred, heat-resistant filler and vinyl triethoxysilane are sequentially added, and the stirring and mixing are continued; then, silane-modified polyurethane, hydrated silica, aminosilane, nano-calcium carbonate, a mixture of barium sulfate and zinc sulfide, a catalyst, ferrosoferric oxide nano-magnetic powder and a color paste are added, and after being evenly stirred, a magnetically controlled repair adhesive is obtained.

7. The preparation method according to claim 6, characterized in that: The preparation method of the silane-modified polyurethane provided comprises: placing a polyether polyol at a temperature of 100-140° C., dehydrating for 2-4 hours, then cooling to 75-85° C., adding a diisocyanate and a catalyst, reacting for 1-3 hours, and detecting the NCO content, and finally adding silane to react until there is no free NCO, thereby obtaining a silane-modified polyurethane; The preparation method of the epoxidized tung oil toughening agent provided comprises: mixing tung oil, petroleum ether, formic acid and a catalyst, heating to 50-55° C., then dripping hydrogen peroxide, continuing to heat to 60-65° C. and keeping the temperature for reaction for 5-7 hours, and purifying the obtained product to obtain the epoxidized tung oil toughening agent; The preparation method of the modified phenolic amine curing agent provided comprises: mixing alkylphenol and polyamine, stirring and heating to 65-75°C, then adding paraformaldehyde, stirring and reacting at a temperature of 65-70°C for 2-4h, and then stirring and reacting at a temperature of 75-80°C for 1-3h to obtain the modified phenolic amine curing agent; The preparation method of the barium sulfate and zinc sulfide mixture provided comprises: mixing zinc and water in a mass ratio of (2-4):1 and heating to a temperature of 65-70°C, adding sulfuric acid to react to obtain a zinc sulfate solution, mixing the zinc sulfate solution with a barium sulfide solution, and adjusting the pH to 7.6-8.0 for precipitation reaction to obtain a barium sulfate and zinc sulfide mixture.

8. The preparation method according to claim 6, characterized in that: During the preparation of the intermediate mixture, the stirring and mixing time is 30-40 minutes.

9. The preparation method according to claim 6, characterized in that: During the preparation of the magnetron repair adhesive, the stirring and mixing time is 30-60 minutes.

10. Use of the magnetically controlled repair adhesive according to any one of claims 1 to 5 in pipeline repair.